A modern operett tánctrendjei a 19. század második felében Offenbach, Párizs és a kánkán - Lengyel Emese; Lengyel Zsanett (2019)
The aim of the study is to examine how French cancan has become one of the most popular dances in the structure of modern operetta. It is a well-known fact that operetta genre has evolved in the 1850s. From 1850, composer Jacques Offenbach has created the new style of musical theatre and the structure of French operetta and its functions. This research focusing on the appearance and the history and also the evolution of a new operetta-dance. Moreover, the Frenchstyle operettas and the Offenbach's operettas are an imprint of a given age, those cultural products including cultural, social and political references. Giving an analysis of Orpheus in the Underworld (1858) and focusing on identify what type of dances could be popular at stage at the age of Offenbach. Thus, we could present the history of cancan and its functions (dance and politics, cancan as a part of the narrative) in that operetta.